Enzyme structure captures four cysteines aligned for disulfide relay. (18th June 2014) - Gat, Yair; Vardi‐Kilshtain, Alexandra; Grossman, Iris; Major, Dan Thomas; Fass, Deborah
Abstract Thioredoxin superfamily proteins introduce disulfide bonds into substrates, catalyze the removal of disulfides, and operate in electron relays. These functions rely on one or more dithiol/disulfide exchange reactions. The flavoenzyme quiescin sulfhydryl oxidase (QSOX), a catalyst of disulfide bond formation with an interdomain electron transfer step in its catalytic cycle, provides a unique opportunity for exploring the structural environment of enzymatic dithiol/disulfide exchange. Wild‐type Rattus norvegicus QSOX1 (RnQSOX1) was crystallized in a conformation that juxtaposes the two redox‐active di‐cysteine motifs in the enzyme, presenting the entire electron‐transfer pathway and proton‐transfer participants in their native configurations. As such a state cannot generally be enriched and stabilized for analysis, RnQSOX1 gives unprecedented insight into the functional group environments of the four cysteines involved in dithiol/disulfide exchange and provides the framework for analysis of the energetics of electron transfer in the presence of the bound flavin adenine dinucleotide cofactor. Hybrid quantum mechanics/molecular mechanics (QM/MM) free energy simulations based on the X‐ray crystal structure suggest that formation of the interdomain disulfide intermediate is highly favorable and secures the flexible enzyme in a state from which further electron transfer via the flavin can occur.